Peran Posyandu dalam Pencegahan Stunting Analisis Efektivitas Program dan Tantangan - Mustain Mustain (https://journal.metanusantara.com/impact/index.php/jpk, 2024)
Stunting is a chronic nutritional problem that affects children's physical growth and cognitive development. Stunting prevention efforts at the village level through the Posyandu programme are one of the effective strategies in reducing stunting rates in Indonesia. This study aims to evaluate the effectiveness of Posyandu mentoring in improving mothers' understanding of balanced nutrition and stunting prevention. This study uses the method ofCommunity Engagement Research (PKM) with a descriptive qualitative approach. Data were collected through in-depth interviews, participatory observation, and document analysis. The research informants consisted of Posyandu cadres, health workers, mothers of children under five, and village heads involved in the programme. Data analysis was conducted thematically with an inductive approach to identify patterns and the effectiveness of the interventions provided.The results showed that Posyandu assistance increased the understanding of mothers under five on the importance of balanced nutrition, from 15% before the programme to 85% after the programme. Success factors include the increased capacity of Posyandu cadres, student involvement as facilitators, and village government support in providing resources. However, challenges are still found, such as low participation of mothers of children under five and limited health workers.